The Diagnostic Shift of SIDS to Undetermined: Are There Unintended Consequences?. Issue 2 (June 2017) - Crandall, Laura Gould; Reno, Laura; Himes, Barbara; Robinson, Deborah
Over the last two decades, a diagnostic shift in regards to the certification of sudden deaths in infancy has emerged with reassignment of deaths previously certified as sudden infant death syndrome (SIDS) to a trend utilizing the classification of undetermined or asphyxia. The consequences of this shift outside the medicolegal death investigation (MDI) community is unknown. We surveyed US organizations working in the field of sudden infant death as well as bereaved parents to understand their perceptions of the current diagnostic trends. Two online anonymous surveys were utilized. Sixty-seven organizations and 55 parents with an infant death diagnosis of SIDS, sudden unexplained infant death (SUID), undetermined, or asphyxia participated. Just over 50% (34/67) of the organizations perceived the shift had an effect on their organization including barriers to bereavement support and education. Forty percent (22/55) of parent respondents stated they did not understand the final diagnosis of their infant's death. The highest frequency of themes elicited from parents were frustration that the diagnosis (regardless of terminology) did not fully explain the death, detrimental mental health effects, and negative perceptions towards the medical and public health communities. However, parents of children whose death was classified as SIDS were spared from negative perceptions towards the medical field, described the least amount of confusion, and reported the most instances of positives effects. Legal implications, perceived social stigmas, and research obstacles were also described. Recommendations from this study include the integration of collaborative efforts to combat sudden infant death with all stakeholders, in and outside of MDI, to achieve better understanding and eradication of these tragedies, improved public education, and effective care of all bereaved.